Pharmaceutical Care Berpengaruh terhadap Kualitas Hidup, Kepatuhan dan Outcome Klinis Pasien Diabetes Melitus Tipe 2 di Beberapa Daerah di Indonesia: Kajian Literatur - Salsabiella, Baiq Rani; Andanalusia, Mahacita (Wiraraja Medika : Jurnal Kesehatan, 2025)
Diabetes mellitus is a metabolic disease in which there are abnormalities in insulin secretion, insulin action or both, causing hyperglycemia. Maximizing pharmaceutical services can be done as a step to improve the quality of life of diabetes mellitus patients and this can be done through pharmaceutical care by pharmacists. This literature review aims to determine the best interventions that can improve the quality of life, compliance and clinical outcomes of diabetes mellitus patients. This paper is the result of a literature review of various studies that examined the effect of pharmaceutical care on the quality of life, compliance and clinical outcomes of type 2 diabetes mellitus patients. A literature search was carried out via the Pubmed and Google Scholar websites using the keywords "pharmaceutical care", "patient quality of life diabetes mellitus", "compliance of type 2 diabetes mellitus patients" "clinical outcomes of type 2 diabetes mellitus patients", "the influence of pharmaceutical care on the quality of life of type 2 diabetes mellitus patients", "the influence of pharmaceutical care on the compliance of type 2 diabetes mellitus patients" "the influence pharmaceutical care on the clinical outcomes of type 2 diabetes mellitus patients" from 2015 to 2023. In this research, 13 research studies were found that were related to the research objectives. The results of the literature review show that counseling, education, Drug Information Services (PIO), telefarma and SMS reminders are the best interventions that can improve compliance, clinical outcomes and quality of life for type 2 diabetes mellitus patients.